Detection of mosaic 15q11.1-q11.2 deletion encompassing NBEAP1 and POTEB in a fetus with diffuse lymphangiomatosis - Chih-Ping Chen; Kuo-Gon Wang; Hsu-Kuang Huang; Cheng-Ran Peng; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Chen-Chi Lee; Wayseen Wang (Elsevier, 2017)
Objective: We present cytogenetic and molecular cytogenetic diagnoses of mosaic deletion of chromosome 15q11.1-q11.2 in a fetus with diffuse lymphangiomatosis. Case Report: A 33-year-old woman underwent amniocentesis at 22 weeks of gestation because of fetal diffuse lymphangiomatosis involving left-side chest, abdominal cavity, thigh and vulva, and intrauterine growth restriction. Amniocentesis revealed a karyotype of 46,XX,del(15) (q11.1q11.2)[9]/46,XX[26]. The mother had a karyotype of 46,XX. The father had a karyotype of 46,XY. The parents elected to terminate the pregnancy. A 610-g female fetus was delivered at 23 weeks of gestation with large cystic lymphangioma over the left abdomen, thigh, and vulva. The umbilical cord had a karyotype of 46,XX,del(15)(q11.1q11.2)[24]/ 46,XX[16]. The placental tissue had a karyotype of 46,XX,del(15)(q11.1q11.2)[23]/ 46,XX[17]. Array comparative genomic hybridization analysis of the umbilical cord and placenta revealed a 2.42-Mb deletion of 15q11.1-q11.2 encompassing the genes of NBEAP1 and POTEB. Conclusion: Deletion of 15q11.1-q11.2 encompassing NBEAP1 and POTEB may be associated with diffuse lymphangiomatosis.